2006
DOI: 10.1159/000091786
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Effect of Combined Treatment with SMP-534 (Antifibrotic Agent) and Losartan in Diabetic Nephropathy

Abstract: Background/Aims: Diabetic nephropathy is now the most common cause of end-stage renal disease. It is also clear that the current therapy, angiotensin II blockage, cannot prevent the progression of diabetic nephropathy. We had previously demonstrated that an antifibrotic agent, SMP-534, reduced extracellular matrix production induced by transforming growth factor-β in vitro, and that SMP-534 prevented renal fibrosis and urinary albumin in diabetic db/db mice via a nonantihypertensive mechanism. We expected that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…We have discovered SMP-534, which inhibits ECM production induced by TGF-β [12], and reported that SMP-534 shows a renoprotective effect in db/db mice independent of the hypoglycemic or antihypertensive effect [13]. Additionally, we reported that the combination of SMP-534 and losartan exerted a renoprotective effect superior to single use because of differences in the mechanism of action [14]. In these studies, we started SMP-534 administration concurrently with the onset of diabetes, demonstrating the efficacy of SMP-534 in preventing diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have discovered SMP-534, which inhibits ECM production induced by TGF-β [12], and reported that SMP-534 shows a renoprotective effect in db/db mice independent of the hypoglycemic or antihypertensive effect [13]. Additionally, we reported that the combination of SMP-534 and losartan exerted a renoprotective effect superior to single use because of differences in the mechanism of action [14]. In these studies, we started SMP-534 administration concurrently with the onset of diabetes, demonstrating the efficacy of SMP-534 in preventing diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…We have also demonstrated that SMP-534 prevents the progression of renal lesions in db/db mice [13] and that combined treatment of SMP-534 and losartan, an antihypertensive agent, prevents the progression of renal lesions in db/db mice more significantly than singular treatment with SMP-534 or losartan [14]. However, in our previous experiments, SMP-534 treatment was started concomitantly with the onset of diabetes, demonstrating the efficacy of SMP-534 treatment in preventing diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…In diabetic patients, treatment with the ACE inhibitor perindopril reduced the intrarenal TGF-expression and activity (Langham et al, 2006). Furthermore, the antifibrotic agent N-acetyl-serylaspartyl-lysyl-proline, which reduced TGF--induced extracellular matrix production and prevented renal fibrosis and albuminuria in diabetic db/db mice, conferred an additional renoprotective effect when combined with the angiotensin II receptor antagonist losartan (Sugaru et al, 2006).…”
Section: Tgf-βmentioning
confidence: 99%
“…[95] Drugs that modify TGFβ expression or reduce TGFβ level 1) ACE inhibitor Perindopril reduces intrarenal TGFβ expression and activity [125] 2) ACE inhibitor reduces serum and urinary level of TGFβ [131] 3) Antifibrotic agent N-acetyl-seryl-aspartyl-lysyl-proline reduced extracellular matrix production, prevented fibrosis and albuminuria in mice model. Also additional renoprotection can be offered when combined with angiotensin II receptor antagonist losartan [130,140] www.wjpps.com 2) Several blocking Abs against TGFβ reduce mesangial matrix accumulation and glomerulosclerosis in diabetic mouse model [75,132] 3) TGF-AY1Ab is in clinical development for the treatment of chronic kidney diseases with focus on diabetic nephropathy. [90] DRUGS-Pirfenidone [133] , Tranilast [134,135] , fresolimumab.…”
Section: ) Albuminuriamentioning
confidence: 99%